Editorial Expression of Concern: Lipid-lowering therapy in patients with coronary heart disease: an Italian real-life survey. Results from the Survey on Risk FactOrs and CardiovascuLar secondary prevention and drug strategieS (SOFOCLES) in Italy - Monaldi Archives for Chest Disease Editors, The (Monaldi Archives for Chest Disease, 2024)
The Editors and the Publisher have been alerted to concerns about this article (DOI: 10.4081/monaldi.2024.2972 ), and an investigation is in progress. In the interim, we alert readers that these concerns have been raised. This Expression of Concern will remain in place until the investigation is completed and any further needs for appropriate action have been taken.